That long silence - Deshpande, Shashi (Haryana Penguin random house, 1989)
Jay's life comes apart at the seams when her husband is asked to leave his job while allegations of business malpractice against him are investigated. Her familiar existence disrupted her husband's reputation in question and their future as a family in jeopardy, Jaya, a failed writer, is haunted by memories of the past. Differences with her husband, frustrations in their seventeen-year-old marriage, disappointment in her two teenage children, the claustrophobia of her childhood and mdash; all begin to surface. In her small suburban Bombay flat, Jaya grapples with these and other truths about herself and mdash; among them her failure at writing and her fear of anger. Shashi Deshpande gives us an exceptionally accomplished portrayal of a woman trying to erase a 'long silence' begun in childhood and rooted in her and in the constraints of her life.